2019
DOI: 10.15453/2168-6408.1612
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Outcomes of Occupational Therapy Students Participating in Community Engaged Learning: A Mixed-Methods Approach

Abstract: Today's health care system requires therapists to acquire a level of confidence, flexibility, and personal growth that enables them to treat a diverse and complex clientele. Occupational therapy programs need to ensure that clinical placements can best prepare students for these demands. Community engaged learning (CEL) offers a distinctive opportunity both to meet the curricular requirements of fieldwork and to afford students the chance to develop unique sets of skills. The purpose of this mixed-methods stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Therefore, each student experience was limited to the particular setting and did not offer a wide perspective regarding the broader contribution of occupational therapy to a community in general. It can be assumed that more opportunities can enable students to address the challenges facing a community [ 23 ], which is necessary for supporting the belief that the role-emerging model may contribute to the need for developing and expanding areas of practice in a community [ 42 ]. These perceptions regarding the importance of community engagement, and the contribution of occupational therapy to a community, need to be further investigated among a larger sample of students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, each student experience was limited to the particular setting and did not offer a wide perspective regarding the broader contribution of occupational therapy to a community in general. It can be assumed that more opportunities can enable students to address the challenges facing a community [ 23 ], which is necessary for supporting the belief that the role-emerging model may contribute to the need for developing and expanding areas of practice in a community [ 42 ]. These perceptions regarding the importance of community engagement, and the contribution of occupational therapy to a community, need to be further investigated among a larger sample of students.…”
Section: Discussionmentioning
confidence: 99%
“…In order to maintain their competency in serving new populations, environments, and systems, students need to be exposed to role-emerging areas during practice placements [ 16 , 17 ]. This may better prepare students to evolve into more diverse and holistic therapists in settings where the role of occupational therapy is undefined [ 23 ]. Role-emerging placements may have advantages, since they can enrich students’ professional and personal growth and development, and allow students to explore, establish, and expand roles in the community [ 17 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of the current study support findings of previous research where community-based learning has been found to be a best practice in higher education pedagogy. These types of experiential learning environments enhance students’ perceptions of knowledge gained and professional growth (Gupta et al, 2021; Mann, 2011; Mattila, 2019; Welch & Carter, 2018). As such, the intergenerational, community-based classroom reviewed in the current study served to grow students’ confidence in their capacity to innovate, modify, and assimilate new information in route.…”
Section: Discussionmentioning
confidence: 99%